2018
DOI: 10.1111/nyas.13961
|View full text |Cite
|
Sign up to set email alerts
|

The role of the dorsal striatum in choice impulsivity

Abstract: It has long been recognized that the dorsal striatum is an essential brain region for control of action selection based on action–outcome contingency learning, particularly when the available actions are bound to rewarding outcomes. In principle, intertemporal choice in the delay‐discounting task—a validated measure of choice impulsivity—involves reward‐associated actions that require the recruitment of the dorsal striatum. Here, we conjecture about ways the dorsal striatum is involved in choice impulsivity. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
34
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 145 publications
(261 reference statements)
3
34
0
Order By: Relevance
“…We therefore tentatively attribute the striatal involvement to the failure of control in the face of personally meaningful incentives. This explanation dovetails with the role of the dorsal striatum in canceling planned motor responses (Bari & Robbins, ; Eagle & Baunez, ) and impulsive choice (Kim & Im, ), while providing evidence for its involvement in additional aspects of impulsivity in humans.…”
Section: Discussionmentioning
confidence: 60%
“…We therefore tentatively attribute the striatal involvement to the failure of control in the face of personally meaningful incentives. This explanation dovetails with the role of the dorsal striatum in canceling planned motor responses (Bari & Robbins, ; Eagle & Baunez, ) and impulsive choice (Kim & Im, ), while providing evidence for its involvement in additional aspects of impulsivity in humans.…”
Section: Discussionmentioning
confidence: 60%
“…Previous studies have shown that the striatum supports the transfer of motivation (e.g., elicited by rewards) to goal-directed behaviors (Báez-Mendoza & Schultz, 2013; Bhanji & Delgado, 2014; Burton, Nakamura, & Roesch, 2015; Kim & Im, 2018; Salamone et al, 2016; Shohamy, 2011; Wang et al, 2013). Extending this previous evidence, we show that the dorsal striatum integrates choice preferences that are elicited by different motivational forces.…”
Section: Discussionmentioning
confidence: 99%
“…Animal studies, for example, have examined basic motivational states (e.g., elicited by food rewards) (Cromwell & Schultz, 2006; Palmiter, 2008; Wang, Miura, & Uchida, 2013). On the neural level, the processing of such basic motivational states and impact on behavioral choices (e.g., place preferences) (Jennings et al, 2013) have been linked to dopaminergic neurons in the striatum (Kim & Im, 2018; Robinson, Sotak, During, & Palmiter, 2006; Salamone & Correa, 2012). In line with these results, human neuroscience studies have shown that the striatum is involved in the processing of different individual motives, as well as motivated choice behaviors, both in the social (Báez-Mendoza & Schultz, 2013; Bhanji & Delgado, 2014) and non-social domain (Salamone et al, 2016; Shohamy, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In the study by de Water and colleagues (2017) in early adolescents, VS activity was positively correlated with a steeper rate of temporal discounting in the VS (de Water, et al, 2017). Given adult work suggesting functional differences across striatal subdivisions in temporal decision-making (Frost & McNaughton, 2017;Kim & Im, 2018), there may be value in examining the specific contributions of the striatal subdivisions to temporal decision-making in adolescents. However, to date, differences among striatal subdivisions have not yet been rigorously examined in adolescents, precluding an understanding of their specific contributions to temporal decision-making.…”
Section: Introductionmentioning
confidence: 99%
“…The striatum in particular is thought to be critically involved in steeper temporal discounting in adults. Enhanced activation in the striatal subdivisions (i.e., ventral striatum [VS], caudate, and putamen) has been associated with more frequent selection of SS options in adult temporal discounting studies (Kim & Im, 2018;Luo, Ainslie, Giragosian, & Monterosso, 2009;McClure, et al, 2007;McClure, et al, 2004). Further, adult studies provide evidence for specific contributions of the striatal subdivisions, with the VS signaling preference and predicting rewards and the caudate evaluating competing reward options during temporal decision-making (Frost & McNaughton, 2017;Kim & Im, 2018).…”
Section: Introductionmentioning
confidence: 99%